Peningkatan Keberanian Siswa Mengemukakan Pendapat melalui Pemberian Penghargaan pada Waktu Diskusi Kelas di SMK Negeri I Balikpapan - Pin Dwi Hantoro (Journal of Education and Religious Studies, 2021)
The inactivity of students in the learning process in the classroom appears in the following: The student's fear of the teacher, the shame of teachers and friends, fear of being wrong in answering teacher questions, less able to compose sentences correctly, and students rarely ask to increase understanding especially in discussion activities. This research was conducted at SMK Negeri 1 Balikpapan Kota Balikpapan, East Kalimantan Province. This research was designed using PTK (Class Action Research) which applies awards in the form of praise and appreciation in the form of grades to overcome the unannction of students in expressing opinions at the time of discussion. The results of the study confirmed that the :P energy of discussion method steps can foster interaction between teachers and students and student interaction with students in Teaching and Learning Activities, which is involved with increasing student activity in asking questions, answering teacher questions, expressing opinions and responding to their friend's answers so that the kbm atmosphere looks alive. The application of award motivation in the form of praise and appreciation in the form of grades can increase students' courage in expressing opinions during class discussions. With the actions of teachers during research activities students can change attitudes from passive to active, this proved 73.4% in this study students dare to express an opinion.